Comparative efficacy of photo-activated disinfection and calcium hydroxide for disinfection of remaining carious dentin in deep cavities: a clinical study - Sidhartha Sharma; Ajay Logani; Naseem Shah (Korean Academy of Conservative Dentistry, 2014)
Objectives To comparatively evaluate the efficacy of photo-activated disinfection (PAD), calcium hydroxide (CH) and their combination on the treatment outcome of indirect pulp treatment (IPT). Materials and Methods Institutional ethical clearance and informed consent of the patients were taken. The study was also registered with clinical registry of India. Sixty permanent molars exhibiting deep occlusal carious lesion in patients with the age range of 18 - 22 yr were included. Clinical and radiographic evaluation and set inclusion and exclusion criteria's were followed. Gross caries excavation was accomplished. In group I (n = 20) PAD was applied for sixty seconds. In group II (n = 20), CH was applied to the remaining carious dentin, while in group III (n = 20), PAD application was followed by CH placement. The teeth were permanently restored. They were clinically and radiographically followed-up at 45 day, 6 mon and 12 mon. Relative density of the remaining affected dentin was measured by 'Radiovisiography (RVG) densitometric' analysis. Results Successful outcome with an increase in radiographic grey values were observed in all three groups. However, on inter-group comparison, this change was not significant (p > 0.05). Conclusions PAD and CH both have equal disinfection efficacy in the treatment of deep carious dentin. PAD alone is as effective for treatment of deep carious lesion as calcium hydroxide and hence can be used as an alternative to CH. They can be used independently in IPT, since combining both does not offer any additional therapeutic benefits.